Contemporary Archaeology as a Framework for Investigating the Impact of Disposable Plastic Bags on Environmental Pollution in Galápagos. (31st December 2020) - Schofield, John; Aylmer, Jerry; Donnelly, Andy; Jones, Jen; Muñoz-Pérez, Juan; Perez, Elena; Scott, Callum; Townsend, Kathy
Abstract : This paper presents contemporary archaeology as a novel framework for investigating environmental pollution, specifically marine pollution, which comprises a global "toxic assemblage" of an estimated 5.25 trillion plastic artefacts. The ideas behind this approach were developed in 2018 during a multidisciplinary "Science to Solutions" workshop held in Galápagos (Ecuador), led by the Galápagos National Park and Galapagos Conservation Trust and hosted by the Galapagos Science Center and the Charles Darwin Research Station. These ideas informed two studies which began separately but became increasingly aligned within a contemporary archaeology framework, in effect tackling the same problem from two very different perspectives: the first involving surface mapping, designed to inform an understanding of how plastic items enter the environment, including the marine environment, in the first place; and the second comprising utilization-focused evaluation, designed to better understand people's behaviours and aspirations. Both of the studies centred on a specific and ubiquitous type of item or artefact: the disposable plastic bag. We conclude that the two studies together demonstrate that, through giving primacy to material culture, contemporary archaeology can (1) serve as a cross-disciplinary framework for tackling environmental pollution, and (2) provide a basis for shaping practice and informing policy.